Birting Ball Exercise terhadap Nyeri Persalinan Kala I - Viki Yusri; Febriyanti Febriyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of the birthing ball on labor pain during the first active phase in women giving birth at the Kurao maternity clinic, Padang. This research uses a quantitative approach with a quasi-experimental non-randomized control group pretest-posttest design. The results showed that the effect of the birth ball method on the intensity of labor pain in the active phase 1 before and after being given the birth ball method obtained moderate pain before providing the process was 1.80. In contrast, after being given the technique, the average pain scale was 1.30 Standard deviation of pain before the method was 0.42, and after being given the standard deviation method 0.38. The results of the statistical test showed a p-value = 0.000. In conclusion, there is a significant effect of providing the birth ball method to reduce the intensity of labor pain in the active first stage. Keywords: Birthing Ball, Pain Intensity, Pelvic rocking, Labor